Intention to marry among single female employees in Malaysia’s financial sector / Nurul Izzati Shuhada Zulkurnain - Nurul Izzati Shuhada , Zulkurnain (2019)
Malaysia has achieved remarkable socio-economic progress over the years and women play an important role in this progress. However, there are issues and concerns in Malaysia regarding the further integration of women in the economy through paid work. The rise in labor force participation has led to a possible shift in attitude towards marriage, including changes in intention to marry and preference among career women toward delayed marriage. These changes are also likely to affect female employees in the financial sector who are career driven and highly educated. Therefore, this dissertation focuses on the single female bank employees and their intention to marry. The results are based on descriptive quantitative and qualitative analysis. The sample comprises 153 respondents who are unmarried female employees, data on whom was collected through a purposefully designed survey of employees of Headquarters (HQ) branches of 12 financial organizations. In addition, this study used in-depth interviews of 20 female bankers to understand employees’ perspectives on marriage. Besides that, this study used a descriptive quantitative analysis based on bi-variate associations, graphical analysis, and cross – tabulations. The analysis of this study shows that work-place demographics play vital role in explaining the intention to stay single among single employees. Female employees that intend to stay single are mostly those who have majority female co-workers, single co-workers, co-workers with Master Degree or co-workers who are divorced and separated mothers and have low work life balance. The quantitative findings are consistent with our qualitative results where respondents highlighted the role of peer factors and bank policies to support work-life balance.